Malaria protein kinase CK2 (PfCK2) shows novel mechanisms of regulation. - Michele Graciotti; Mahmood Alam; Lev Solyakov; Ralf Schmid; Glenn Burley; Andrew R Bottrill; Christian Doerig; Paul Cullis; Andrew B Tobin (PLoS ONE)
Casein kinase 2 (protein kinase CK2) is a conserved eukaryotic serine/theronine kinase with multiple substrates and roles in the regulation of cellular processes such as cellular stress, cell proliferation and apoptosis. Here we report a detailed analysis of the Plasmodium falciparum CK2, PfCK2, demonstrating that this kinase, like the mammalian orthologue, is a dual specificity kinase able to phosphorylate at both serine and tyrosine. However, unlike the human orthologue that is auto-phosphorylated on tyrosine within the activation loop, PfCK2 shows no activation loop auto-phosphorylation but rather is auto-phosphorylated at threonine 63 within subdomain I. Phosphorylation at this site in PfCK2 is shown here to regulate the intrinsic kinase activity of PfCK2. Furthermore, we generate an homology model of PfCK2 in complex with the known selective protein kinase CK2 inhibitor, quinalizarin, and in so doing identify key co-ordinating residues in the ATP binding pocket that could aid in designing selective inhibitors to PfCK2.